Garbo lacht: Revolution und Melancholie in Lubitschs Ninotschka - Jukić, Tatjana (Array, 2013)
Taking up Ninotchka as the point of departure, I argue that Garbo works in Lubitsch where she designates for the cinema a peculiar critical intelligence. It is around this intelligence that Lubitsch then organizes his exploration of the political and of comedy as the platform where the crisis decisive to the political is addressed. This crisis presents itself in the Lubitsch narrative as a complex intersection of the imaginaries of masochism and melancholia, indeed as a kind of masochism cum melancholia. As such, Ninotchka in turn provides a position from which to reassess the attempts to analyze the political along the joint lines of philosophy and psychoanalysis, in authors seemingly as different as Gilles Deleuze and Stanley Cavell.